Odpowiedzi

2010-02-04T16:06:34+01:00
A)
{6(x+y)=10y
{y-x=0,5 -> y= x+0,5

{6x+6y=10y
{y= x+0,5

{6x=4y
{y= x+0,5

{6x=4 (x+0,5)
{y= x+0,5

{6x=4x+2
{y= x+0,5

{2x=2 /2
{y= x+0,5

{x=1
{y= x+0,5

{x=1
{y= 1+0,5

{x=1
{y= 1,5

b)
{10(y+2)+3(x-5)=x-5
{25(y+2)+3(x-5)=-10

{10y+20+3x-15=x-5
{25y+50+3x-15=-10

{10y+2x=-10 /2
{25y+3x=-45

{5y+x=-5 /2 -> x = -5-5y
{25y+3x=-45

{x = -5-5y
{25y+3(-5-5y)=-45

{x = -5-5y
{25y-15-15y=-45

{x = -5-5y
{10y=-30 / 10

{x = -5-5y
{y=-3

{x = -5-5 *(-3)
{y=-3

{x = 10
{y=-3